BPMA celebrates 75th anniversary. Issue 1 (January 2016) - Reynolds, Peter
Abstract : To commemorate 75 years, the British Pump Manufacturers Association is producing a number of articles on key developments in the British pump industry and how the BPMA played its part. Here, president Peter Reynolds of Grundfos Pumps Ltd. starts the story.